Characterization of a novel pathway for xanthene degradation by the engineered strain Sphingobium yanoikuyae B1DR (Baghdad Science Journal, 2023)
Polyaromatic hydrocarbons (PAHs) are a group of aromatic compounds that contain at least two rings. These compounds are found naturally in petroleum products and are considered the most prevalent pollutants in the environment. The lack of microorganism capable of degrading some PAHs led to their accumulation in the environment which usually causes major health problems as many of these compounds are known carcinogens. Xanthene is one of the small PAHs which has three rings. Many xanthene derivatives are useful dyes that are used for dyeing wood and cosmetic articles. However, several studies have illustrated that these compounds have toxic and carcinogenic effects. The first step of the bacterial degradation of xanthene is conducted by dioxygenase enzymes that introduces two oxygen atoms in the structure of the aromatic rings. In this study we focused on the bacterial bioremediation of xanthene via Sphingobium yanoikuyae B1DR, an engineered strain carrying the dioxin angular dioxygenase from Sphingomonas wittichii RW1. HPLC analysis of supernatant from resting cells of S. yanoikuyae B1DR grown on xanthene and succinate showed the ability of this strain to transform xanthene to 2-hydroxyphenylacetate that was not produced by the wild type of Sphingobium yanoikuyae B1. Production of 2-hydroxyphenylacetate was confirmed by GC-MS. Our results show the importance of this strain in reducing the toxic effects of xanthene in the environment and showed for the first time that ring-hydroxylation enzymes and hydrolases for biphenyl degradation in S. yanoikuyae B1 may function on metabolites generated from the degradation pathway of xanthene. By analyzing our results we were able to draw a novel pathway for xanthene degradation in S. yanoikuyae B1DR.